2012
DOI: 10.1055/s-0032-1319917
|View full text |Cite
|
Sign up to set email alerts
|

Personal, Psychosocial, and Occupational Resources for Preventing Persistent Low Back Pain in Primary Care

Abstract: Introduction Socioeconomic costs of persistent low back pain (LBP) exceed the costs of acute and subacute LBP by far. This makes the early identification of modifiable factors of the progression of acute/subacute LBP essential to the persistent state. Modifiable protective factors could be addressed proactively, for example, in workplace interventions, to limit the associated socioeconomic burden. Aim of our study was to identify modifiable protective factors against the progression of acute/subacute LBP to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A possible interpretation may be that high job demand such as maximum workload and short deadlines was likely to increase hurried movements with high accelerations or poor posture. Additionally, some studies have found support for the association of low social support with LBP [ 70 , 71 , 72 ]. In contrast, our study indicated no direct relation between social support and LBP, which was similar to the studies from the Sterud and Hartvigsen [ 66 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible interpretation may be that high job demand such as maximum workload and short deadlines was likely to increase hurried movements with high accelerations or poor posture. Additionally, some studies have found support for the association of low social support with LBP [ 70 , 71 , 72 ]. In contrast, our study indicated no direct relation between social support and LBP, which was similar to the studies from the Sterud and Hartvigsen [ 66 , 73 ].…”
Section: Discussionmentioning
confidence: 99%